EQUIVALENCE THEOREM FOR GENERALIZED DEPENDENCIES IN RELATIONAL DATABASES - Nguyễn Xuân Huy; Trương Thị Thu Hà (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, we present some new results related to the differential dependencies in relational databases. The main contributions are the following: (1) To introduce a new concept of generalized differential dependencies; (2) To claim and proof the equivalence theorem of consequences in the world of all relations, the word of two-tuple relations and propositional logic for the generalized differential dependencies; (3) To show an equivalence between generalized positive Boolean dependencies and generalized differential dependencies.